Kemampuan Membaca dan Karakter Siswa Kelas III di SD Negeri Palamba Langowan Selatan - Nurfadillah Rahman; Supriadi, Supriadi; Nurdiansyah, Erwin; Erniati, Erniati; Arief , Herawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
This research aims to find out the reading ability and character of class III students at SD Negeri Palamba Langowan Selatan. This research is a qualitative descriptive research. The instruments used in this research were observation, interviews and documentation. The data analysis technique used is the triangulation method. The results of the research provide a solution for third grade students who are lacking in learning to read and their character in everyday life, by providing a different reading method, namely by providing reading through story books so that students do not get bored in the learning process which is carried out using this method. new materials given to students are able to increase students' interest in reading.